Ð‘ÐµÐ»ÐºÐ¸-Ð½ÑƒÐºÐ»ÐµÐ°Ñ‚Ð¾Ñ€Ñ‹ Ð±Ð°ÐºÑ‚ÐµÑ€Ð¸Ð°Ð»ÑŒÐ½Ð¾Ð³Ð¾ Ð¿Ñ€Ð¾Ð¸ÑÑ…Ð¾Ð¶Ð´ÐµÐ½Ð¸Ñ. Ð¡Ð¾Ð¾Ð±Ñ‰ÐµÐ½Ð¸Ðµ III. Ð ÐµÐ³ÑƒÐ»ÑÑ†Ð¸Ñ Ð°ÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚Ð¸ Ð¸ Ð·Ð½Ð°Ñ‡ÐµÐ½Ð¸Ðµ Ð² Ð¿Ñ€Ð¸Ñ€Ð¾Ð´Ðµ Ð¸ Ð±Ð¸Ð¾Ñ‚ÐµÑ…Ð½Ð¾Ð»Ð¾Ð³Ð¸Ð¸ - Gulevsky, A. K.; Relina, L. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2010)
The information that has been gathered so far on the regulation of bacterial nucleation protein activity is presented in the review; the main fields of applications of biological nucleators and their encoding genes in biotechnology are discussed.